CHILDREN'S RIGHTS AND ANIMAL WELFARE - Vučković Šahović, Nevena; Burazerović, Elvir (Zbornik radova Pravnog fakulteta u Nišu, 2020)
In the light of the 30thanniversary of the Convention on the Rights of the Child (CRC) and the ever-changing social, economic, cultural and natural environments at the global level, animal welfare should become an emerging topic to be included and should broaden the understanding of the CRC application. Animal welfare can be understood as a mechanism to directly affect and ensure the following children’s rights: the right to life, survival and development (Article 6), the right to health (Article 24), the right to food (Articles 27 and 24), the right to protection against all forms of violence (Articles 19 and 31), the right to recovery of victims (Article 39), the rights in relation to the aims of education (Article 29), the right to leisure and play (Article 31), and the right to a healthy environment. The paper elaborates how the provision of a good state of animal welfare affects the exercise of selected children’s rights: the right to health and the right to protection against all forms of violence. There is a growing body of evidence for positive effects of good state of animal welfare on the exercise of children’s rights on a global level. It is of broader social importance to recognize this interconnection and understand mechanism by which treating animals with care is reflected on the welfare of the child and the exercise of their rights.